Pengaruh Media Sosial Instagram Terhadap Perubahan Dalam Gaya Hidup Gen Z di Kota Tangerang - Siregar, Delani; Aditya, Toddy; Purwanto, Eko; Elyana, Korry (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Instagram is a social media platform that has many users, mostly teenagers. Instagram is currently playing a role in changing the lifestyle of Generation Z, but it does not always have a positive impact because some users are negatively impacted. Instagram is changing the lifestyle of Generation Z. Change depends on everyone using Instagram. The research utilizes a quantitative method approach, applying techniques, SPSS version 24 software to analyze questionnaire data collected via Excel. Stages: Validity and Reliability Test, Regression Test, Correlation Test, Determination Test and t Test. The research results prove influencing factors such as visual communication, interaction relations, personalization, network relations, and information delivery. has a negative and positive correlation with lifestyle changes in gen z. 27 statements were shown to be valid and reliable because the table r value was greater than the calculated r value and reliability value. The r2 value in the coefficient of determination test is 25.9% indicating the digital media variable (Independent) on the lifestyle change variable of gen z. The research results show that factors have a big influence on changes in Gen Z's lifestyle, both positive and negative.